Comparative Interpretation of Verses About the Meaning of Tartil in Tafsir Al-Qurtubi, Tafsir Ibn Katsîr, and Tafsir Sayyid Qutb - Tatan Setiawan; Asep Fathurrohman (UIN Sunan Gunung Djati Bandung, 2022)
This article compares the meaning of Tartil lafazh and its derivation in the Qur'an from the perspective of al-Qurtubi, Ibn Kathir and Sayyid Qutb. The purpose of this study is to understand the comparison of the meaning of Tartil lafazh and its derivation in the interpretations of al-Qurtubi, Ibn Kathir, and Sayyid Qutb. The writing of this research article uses a literature-based analytical descriptive method. The results of this study conclude that, in the interpretation of al-Qurthubî to surah al-Muzzammil verse 4, Tartil is an unhurried reading, slowly and accompanied by contemplating the meaning contained in it. Al-Qurtubi forbids reading the Qur'an, which is sung. According to Ibn Kathir, Tartil is interpreted as an unhurried reading of the Qur'an to assist in understanding the contents of the Qur'an and decorate the task with hums and songs with beautiful voices. As for Sayyid Qutb's opinion, Tartil understands the meaning of what is read while keeping the reading short, not excessively singing it and humming it. Then the purpose of Tartil in Surah al-Furqân verse 32, according to al-Qurtubi is the regular and correct reading. Meanwhile, according to Ibn Kathir is to explain clearly, and according to Sayyid Qutb is a continuous and successive reading regularly. The background to the differences in the interpretation of the three commentators is the difference in the period of the birth of the interpretation, the different sources of interpretation, the different styles and schools of interpretation, and the differences in the specific methods of interpretation.